LAW ENFORCEMENT ANALYSIS REGULATIONS FOR USING TELEPHONE WHILE DRIVING AGAINST ONLINE OJEK IN BANDAR LAMPUNG - Rissa Afni Martinouva (Indonesia Private Law Review, 2021)
Road users other than online public transportation must also be given legal protection and together enjoy the convenience of traffic facilities. Drivers are required to concentrate while driving a vehicle. This is regulated in Law Number 22 of 2009 concerning Road Transportation Traffic, Article 106 that everyone driving a motorized vehicle on the road is obliged to drive his vehicle fairly and with full concentration. The observations made were that attaching a communication device to online public transportation proved that the telephone was used while driving a vehicle. Communicating by telephone while driving a vehicle will cause an accident that will harm other road users. This study discusses the regulations for using the telephone while driving against online motorcycle taxis and law enforcement analysis the regulations for using the telephone while driving against online motorcycle taxis in Bandar Lampung. The results showed the telephone regulations while driving to online motorcycle taxis in Bandar Lampung were Permenhub No. 12 of 2019 Article 4, Article 6, Article 17, Article 18, and Article 19. The results of the analysis of law enforcement on the use of telephones while driving in the form of online motorcycle taxis to contact consumers on their way to the location 3 (three) times, namely 32% (thirty-two per cent) and the intensity of online motorcycle taxis to contact consumers more than 3 (three) times, namely 27% (twenty-seven percent). The analysis data has proven that the intensity of contacting passengers is very much done while driving. Online motorcycle taxi drivers do not obey the rules because they communicate more by telephone while driving.